Forestillinger om kvalitet og tværfaglighed på sygehuse: Skabelse af forestillinger i læge- og plejegrupperne angående relevans af nye idéer om kvalitetsudvikling gennem tolkningsprocesser - Jens Albæk (Copenhagen Business School (CBS), 2009)
– The aim of this dissertation is to identify how ideas of organisational development are incorporated into and employed in hospital departments. The dissertation focuses on the conceptions of professional identity among doctors and nurses, their conceptions of clinical practice and the ideas of development they are introduced to. The health professionals' conceptions of development and practice are connected to their perception of `professional relevance' in the dissertation. This conception of `professional relevance' thereby forms a recurring expression of conceptions among the actors.
hdl:10398/7806
Keywords: 650